2009 IEEE/AIAA 28th Digital Avionics Systems Conference 2009
DOI: 10.1109/dasc.2009.5347535
|View full text |Cite
|
Sign up to set email alerts
|

Sectorless ATM — A concept to increase en-route efficiency

Abstract: Feasibility of a new air traffic management concept is examined which might increase the efficiency of en-route operations by up to 100%. The concept follows the idea of a sector-less airspace organization. Aircraft entering the airspace (e.g. the German airspace or the entire European Airspace) will be assigned to one controller who is in charge of controlling the aircraft from entry point (or TMA exit point) to exit point of the airspace (or TMA entry point). First simple real time simulations revealed very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 1 publication
0
23
0
Order By: Relevance
“…Currently the concept is investigated further in the research project LRM2020. The present state of research has been reported by Korn et al [6] and Pütz et al [7].…”
Section: The Concept Of Sectorless Atmmentioning
confidence: 85%
See 2 more Smart Citations
“…Currently the concept is investigated further in the research project LRM2020. The present state of research has been reported by Korn et al [6] and Pütz et al [7].…”
Section: The Concept Of Sectorless Atmmentioning
confidence: 85%
“…The simulations showed that in principle it is possible to control air traffic in such a way and that various benefits can be expected from such an approach. For a detailed description of the simulations and their results see Korn et al [6].…”
Section: Figure 1 Sectored and Sectorless Airspacementioning
confidence: 99%
See 1 more Smart Citation
“…However, not every aircraft produces the same workload-level changes or a high probability of conflict resolution activities tend to produce higher ATCO workload. Therefore, the second distribution strategy chosen is the uniform allocation of ATCO workload (2). Workload is an important part for the sectorized concept in determining sector capacity needed by the air traffic flow management (ATFM), which is described in [6] and [7].…”
Section: Selection Of Strategies and Their Complexitymentioning
confidence: 99%
“…Figure 1 depicts the main elements of the concept and how they interact with each other. The concept itself, the simulation environment and some first results are presented in [2] and (Pütz 2009 ''Handbuch für das sektorlose Lotsenkonzept--Luftraummanagement 2020'' V1.3 DFS). The module of Flight Plan Processing creates the initial 4D-profiles and sends them with some updates for previous profiles to the Assignment Center module.…”
Section: Introductionmentioning
confidence: 99%